The Role Of Social Media In Disseminating Health Awareness Among Students Living In Damascus University’s Campus During The COVID-19 Pandemic (Damascus University Journal of educational and Psychologyical sciences, 2024)
This study aimed to explore the role of social media in spreading health awareness in light of the COVID-19 pandemic, and to achieve the goal of the study, the researcher prepared a questionnaire consisting of two parts: the first section included personal data, and the second section consisted of (25) items applied to a sample consisting of (1007) students during the second semester of the academic year 2021-2020.The results of the study showed that social media played an intermediate role in spreading health awareness in light of the COVID-19 pandemic among university students in Damascus.The results of the study did not show that there were statistically significant differences between the average scores of students with regard to the role of social media in spreading health awareness, according to the variable of academic qualification and gender.
Keywords: Health Awareness, University City; Corona Pandemic